2019
DOI: 10.3390/antiox8060185
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Berberine in Berberis vulgaris L. Root Extract and Its Curative and Prophylactic Role in Cisplatin-Induced In Vivo Toxicity and In Vitro Cytotoxicity

Abstract: Cisplatin is amongst the most potent chemotherapeutic drugs with applications in more than 50% of cancer treatments, but dose-dependent side effects limit its usefulness. Berberis vulgaris L. (B. vulgaris) has a proven role in several therapeutic applications in the traditional medicinal system. High-performance liquid chromatography was used to quantify berberine, a potent alkaloid in the methanolic root extract of B. vulgaris (BvRE). Berberine chloride in BvRE was found to be 10.29% w/w. To assess the prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Cisplatin can induce activation of the pro-apoptotic proteins, which form pores in the outer membrane of mitochondria, resulting in induction of cytochrome c release into cytosol and resultant activation of executioner caspases such as caspase-3. Previous studies have shown that in addition to its anti-oxidant and radical-scavenging properties, melatonin exerts an anti-apoptotic effect on various types of cells [13,25]. In this study, we found that melatonin greatly inhibited caspase-3 activation and subsequent cleavage of PARP-1 in kidneys after cisplatin injection.…”
Section: Discussionsupporting
confidence: 61%
“…Cisplatin can induce activation of the pro-apoptotic proteins, which form pores in the outer membrane of mitochondria, resulting in induction of cytochrome c release into cytosol and resultant activation of executioner caspases such as caspase-3. Previous studies have shown that in addition to its anti-oxidant and radical-scavenging properties, melatonin exerts an anti-apoptotic effect on various types of cells [13,25]. In this study, we found that melatonin greatly inhibited caspase-3 activation and subsequent cleavage of PARP-1 in kidneys after cisplatin injection.…”
Section: Discussionsupporting
confidence: 61%
“…In this study, we found that administration of SRT1720 ameliorates acute renal failure in cisplatin-treated mice, as represented by decreased levels of creatinine and BUN. Because cisplatin treatment induces structural damages in kidneys, especially tubular injuries [25,26,27], we further examined the effect of SRT1720 on levels of NGAL and Kim-1. We found that tubular injuries in kidneys of cisplatin-treated mice were also markedly prevented by SRT1720, as evidenced by reduced expression of NGAL and Kim-1.…”
Section: Discussionmentioning
confidence: 99%
“…As a promising drug, various pharmacological activities of berberine have been reported, including antimicrobial, antiemetic, antipyretic, anti-pruritic, antioxidant, anti-inflammatory, hypotensive, anti-arrhythmic, and sedative activities (Shamsa et al, 1999;Chen et al, 2012;Caliceti et al, 2016). Several reports have mentioned that berberine shows nephroprotective effects against cisplatin-induced kidney damage (Domitrović et al, 2013;Teng et al, 2015;Ojha et al, 2016;Ahmad et al, 2019). However, the mechanism of alleviating CI-AKI is still unclear.…”
Section: Introductionmentioning
confidence: 99%